(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Aim: The aim was to develop a low cost multi use body level hearing aid (HA) targeting the Asian population. Method: The study began with need identification. In this stage the researcher wanted to identify the changes which the parents and professionals thought would improve the functionality of the present say body level hearing aids. A survey of 106 hearing aid users, parents and professionals was done. All had been exposed to hearing aids since five years or more. They were asked to name one change which can be incorporated into the present day HA aids to increase its functionality and utility. Six major changes were significantly (pd 0.05) recommended. The changes were considered to develop a prototype which was then field tested for its efficacy. Results: the six changes which were identified by the 106 participants included incorporating better cords, better battery backup, easy repair facilities, low battery indicator, torch facilities along with a vibrating alert. A prototype was developed at a very low cost of 936 rupee with facilities of a strong class HA, vibrating doorbell alert, rechargeable battery, torch light and a vibrating doorbell alert and a low battery indicator. It was found to function satisfactorily and won the prestigious Sushrut Innovation award by the Department of Science and Technology, India for year 2011. Conclusions: the developed prototype can be considered for large scale production. It would bring down the cost of the prototype and beneficiaries would get an advantage of assistive devices along with the hearing aid. DOI: http://dx.doi.org/10.3329/bjo.v18i1.10412 Bangladesh J Otorhinolaryngol 2012; 18(1): 36-41